Pendampingan Pengembangan Karakter Islami Anak Dan Kemampuan Menulis huruf hijaiyah Melalui Kegiatan Baca Tulis Pegon Dari Kitab Tarih Nabi di Desa Butuh – Kras – Kediri - Sadiyatul Masadah; Khoirotul Izzah (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2020)
Childhood is a golden period in the formation of the crust, because children will naturally have a personality in accordance with what always happens in their daily lives. Children who live in an Islamic environment will have an Islamic character, and vice versa. In addition, children tend to be more receptive to learning if delivered in an interesting way according to them, not a few of them are always interested if told a story. Because at their age they tend to prefer to listen to something new. Therefore, researchers have an initiative to research the development of children's Islamic character and the ability to write hijaiyah letters through reading pegon writing activities from the prophet's tarih book. Which is the prophet's date book is a book filled with inspiring stories of prophets, who are expected to be able to develop the islamic character of children.